HUBUNGAN STATUS GIZI DAN LEVEL AKTIVITAS FISIK DENGAN TINGKAT KEBUGARAN PADA PEMAIN BOLA BASKET DI UKM BASKET - Nimrot Manalu; Hernaldi Josua Sihombing; Mulia Rahman; Muhammad Agung Firmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Basketball requires physical endurance, speed, and high energy expenditure. Students often experience low fitness levels due to lack of physical activity, which can hinder their athletic performance. Irregular food and beverage consumption can also affect nutritional status. Techniques and training without adequate nutritional support will not achieve optimal performance. This study aims to examine the relationship between nutritional status and physical activity with the fitness levels of basketball players in the basketball student activity unit (UKM Basket). This study used a cross-sectional design. A sample of 40 people was randomly selected using simple random sampling. Data collection included nutritional status with weight and height measurements, a physical activity questionnaire, and fitness level measurements using the bleep test method. Data analysis used Pearson correlation. The majority of respondents had normal nutritional status (85.7%) for men and 84.1%) for women. The majority of respondents had high physical activity (52.4%) for men and 73.7%) for women. Meanwhile, the fitness level of the majority was good (28.5%) for men and 26.3%) for women. There was a relationship between physical activity (p=0.049) and fitness levels, while there was no significant relationship between nutritional status and fitness levels in basketball players (p=0.693). Physical activity is related to fitness levels, while nutritional status is not related to fitness levels in basketball players. Basketball players should monitor their nutritional status (BMI) along with regular physical activity, such as exercise, in their daily lives. Good nutritional status alone, without physical activity, will not improve fitness levels.